Targeting hepatic pyruvate dehydrogenase kinases restores insulin signaling and mitigates ChREBP-mediated lipogenesis in diet-induced obese mice - Cheng-Yang Wu; Shih-Chia Tso; Jacinta L. Chuang; Wen-Jun Gui; Mingliang Lou; Gaurav Sharma; Chalermchai Khemtong; Xiangbing Qi; R. Max Wynn; David T. Chuang (Molecular Metabolism, 2018)
Objective: Mitochondrial pyruvate dehydrogenase kinases 1–4 (PDKs1–4) negatively regulate activity of the pyruvate dehydrogenase complex (PDC) by reversible phosphorylation. PDKs play a pivotal role in maintaining energy homeostasis and contribute to metabolic flexibility by attenuating PDC activity in various mammalian tissues. Cumulative evidence has shown that the up-regulation of PDK4 expression is tightly associated with obesity and diabetes. In this investigation, we test the central hypothesis that PDKs1-4 are a pharmacological target for lowering glucose levels and restoring insulin sensitivity in obesity and type 2 diabetes (T2D). Methods: Diet-induced obese (DIO) mice were treated with a liver-specific pan-PDK inhibitor 2-[(2,4-dihydroxyphenyl) sulfonyl]isoindoline-4,6-diol (PS10) for four weeks, and results compared with PDK2/PDK4 double knockout (DKO) mice on the same high fat diet (HFD). Results: Both PS10-treated DIO mice and HFD-fed DKO mice showed significantly improved glucose, insulin and pyruvate tolerance, compared to DIO controls, with lower plasma insulin levels and increased insulin signaling in liver. In response to lower glucose levels, phosphorylated AMPK in PS10-treated DIO and HFD-fed DKO mice is upregulated, accompanied by decreased nuclear carbohydrate-responsive element binding protein (ChREBP). The reduced ChREBP signaling correlates with down-regulation of hepatic lipogenic enzymes (ACC1, FAS, and SCD1), leading to markedly diminished hepatic steatosis in both study groups, with lower circulating cholesterol and triacylglyceride levels as well as reduced fat mass. PS10-treated DIO as well as DKO mice showed predominant fatty acid over glucose oxidation. However, unlike systemic DKO mice, increased hepatic PDC activity alone in PS10-treated DIO mice does not raise the plasma total ketone body level. Conclusion: Our findings establish that specific targeting of hepatic PDKs with the PDK inhibitor PS10 is an effective therapeutic approach to maintaining glucose and lipid homeostasis in obesity and T2D, without the harmful ketoacidosis associated with systemic inhibition of PDKs. Keywords: Pyruvate dehydrogenase kinase inhibitor, Liver, Glucose homeostasis, Insulin sensitivity, Hepatic steatosis, ChREBP